Strategi Digital Marketing untuk Meningkatkan Kesadaran Merek dan Niat Beli Pelanggan di Bonassa Collection, Kabupaten Gresik - Dara, Rizqi Aprilia (Jurnal Bisnis Indonesia, 2024)
BonaSSa Collection is a business unit based in the city of Surabaya and has a branch in GresikRegency. This business operates in the fashion sector, especially Muslim clothing, with a targetmarket of children to adults, both women and men. The main problem with the BonaSSa CollectionGresik Regency branch is low brand awareness and low customer purchase intention from the targetmarket. The research methodology uses qualitative research. This research aims to help increasebrand awareness and purchasing intentions of their potential customers. Data collection was carriedout using an interview system with respondents who were business owners and employees at theGresik Regency branch. Based on these results, respondents' brand awareness is low, as is customerpurchase intention. It was found that the digital media recommended for use by respondents weresocial media Instagram, Facebook, Tiktok, WhatsApp, Shopee, search engines and websites. Based onthese results, BonaSSa Collection is able to optimize Search Engine Optimization (SEO) which issupported by a website optimizer and attractive content marketing, create and optimize the use ofsocial media and Shopee.Keywords: Digital Marketing; Social Media Marketing; Brand Awareness; Customer PurchaseIntention.